Stearoyl-CoA Desaturase (SCD) Gene Diversity and Its Association with Fatty Acids in Bali Cattle Using PCR-RFLP Method - Sarwi, Annisa; Noor, Ronny Rachman; Jakaria, Jakaria (Jurnal Ilmu-Ilmu Peternakan, 2025)
This study examines the Stearoyl-CoA desaturase (SCD) gene, which is essential for converting saturated fatty acids (SFA) into monounsaturated fatty acids (MUFA). The research aims to analyze the diversity of Single Nucleotide Polymorphism (SNP) g.10428C>T within the SCD gene using the PCR-RFLP method. The investigation involved 40 blood samples from male Bali cattle aged 1.5 to 3 years, sourced from the Banjarmasin Slaughterhouse (RPH) in South Kalimantan. The SNP g.10428C>T diversity in the SCD gene was analyzed using the PCR-RFLP technique with the HinfI restriction enzyme. Genotype frequencies, allele frequencies, heterozygosity values, and the Hardy-Weinberg equilibrium were calculated using Popgen32. The relationship between fatty acid composition and the genotype of the SCD gene, as well as the fatty acids in Bali beef, was analyzed using a t-test. SCD|HinfI was found to have homozygous CC (0.03) and TT (0.85) and heterozygous CT (0.13) genotypes with a C allele frequency of 0.09 and T of 0.91. SNP g.10428C>T in the SCD gene was not significantly associated with fatty acid composition.